Jesus, gnosis and dogma - Roukema, Riemer (London ; New York : T & T Clark, 2010)
In Jesus, Gnosis and Dogma Roukema investigates and assesses the various views of Jesus in early Christianity, basing his approach on a distinction between historical and theological statements about Jesus. Historical statements can be arrived at through a critical study of the earliest records, although Roukema recognizes that scholars differ widely here. Theological statements about Jesus are to do with what has been and is believed about him. Roukema demonstrates that Gnostic traditions about Jesus mostly derive from the earlier traditions preserved in the New Testament writings and do not
Introduction -- Jesus' origin and identity -- Jesus' teaching -- Jesus' death, resurrection and exaltation -- Interim conclusions and new questions -- Jewish Christianity -- Did Jesus have a secret teaching? -- Does Jesus as Lord and son of God fit into early Judaism? -- Jesus and the dogma of God's Trinity -- Conclusions and evaluation.
Includes bibliographical references (p. 199-216) and indexes.
Description based on print version record.
Keywords: Jesus Christ -- Person and offices; Gnosticism; Jesus Christ -- Gnostic interpretations; Jesus Christ -- Biography -- Sources, Biblical; Jesus Christ -- History of doctrines -- Early church, ca. 30-600.; Religion; RELIGION -- Christian Theology -- Christology; Electronic books